Predimensionamiento sistema séptico para vivienda rural dispersa vereda el Carmen municipio de Duitama, Boyacá (2023)
The primary purpose of the research project is the evaluation of the effectiveness of a septic system, through which it seeks to mitigate the pollution factors associated with the inadequate management of wastewater from dispersed rural homes and its final disposal, especially the lack of of a septic system. The focus of this predimensioning is carried out in the rural area, in the village of El Carmen in the municipality of Duitama, in the department of Boyacá. In order to propose an alternative solution to the problem evidenced, four phases were implemented in the development for the pre-dimensioning of the septic system. Beginning is the collection and analysis of bibliographic information from existing studies for the pre-sizing of a septic tank. In the second phase, the observation stage of the considerations for the pre-dimensioning of the septic system is covered, which are described in the general files corresponding to each component of the septic system, when it comes to dispersed rural housing based on the Technical Regulation of the sector of drinking Water and Basic sanitation, Resolution 0799 of December 09, 2021. In the third phase, the way to evaluate the effectiveness of the pre-sizing of the septic tank is presented through the use of Excel and other tools that allow concise data to be obtained. As a solution we can say that the systems or septic tanks are an alternative which provides adequate basic sanitation to dispersed rural homes since in these areas they are difficult to access so that they can have a sewage network.